Challenging Stigma: The Performative Strategies of Janger Artists in Banyuwangi - Dear Lova Sukoco; Rosnida Sari (Journal of Feminism and Gender Studies, 2025)
This study focuses on the dynamics of self-image among female artists in the traditional Janger performance group, Sri Budoyo Pangestu (SBP), Banyuwangi, using Erving Goffman's dramaturgical approach. The main objective of the research is to explore how women as Janger performers overcome the social stigma attached to their profession. The study employs a qualitative method with a phenomenological approach. The findings reveal that the negative stigma toward female Janger artists—particularly the stereotypes of being "vulgar" or "erotic"—has prompted them to develop self-image strategies through the concepts of front stage and back stage. The front stage represents the artists’ efforts to create a positive impression in the eyes of the audience, while the back stage provides a space for them to step away from their artistic roles and live their personal lives. In this context, Lilis, as the leader of the SBP Janger troupe, plays a vital role in upholding ethics and professionalism among group members. The study concludes that the dramaturgical strategies employed by female Janger performers have successfully shaped a positive self-image despite strong societal stigma. This indicates that traditional performing arts can serve as a space for women to demonstrate professionalism and maintain personal dignity.